Thermal Characterization of European Ant Communities Along Thermal Gradients and Its Implications for Community Resilience to Temperature Variability - Arnan, Xavier; Blüthgen, Nico; Molowny-Horas, Roberto; Retana, Javier (Frontiers in Ecology and Evolution, 2015)
Ecologists are increasingly concerned about how climate change will affect biodiversity yet have mostly addressed the issue at the species level. Here, we present a novel framework that accounts for the full range and complementarity of thermal responses present in a community; it may help reveal how biological communities will respond to climatic (i.e., thermal) variability. First, we characterized the thermal niches of 147 ant species from 342 communities found along broad temperature gradients in western Europe. Within each community, species’ mean thermal breadth and the difference among species’ thermal optima (thermal complementarity) were considered to define community thermal niche breadth—our proxy for community thermal resilience. The greater the range of thermal responses and their complementarity within a community, the greater the likelihood that the community could cope with novel conditions. Second, we used simulations to calculate how robust community thermal resilience was to random species extinctions. Community resilience was considered to be robust when random species extinctions largely failed to constrict initial community thermal breadth. Our results indicate that community thermal resilience was negatively and positively correlated with mean temperature and temperature seasonality, respectively. The pattern was reversed for robustness. While species richness did not directly affect community resilience to thermal variability, it did have a strong indirect effect because it determined community resilience robustness. Consequently, communities in warm, aseasonal regions are the most vulnerable to temperature variability, despite their greater number of species and resultant greater resilience robustness.